FACTORS FOR INCREASING THE PRESTIGE OF THE UZBEK LANGUAGE AS A STATE LANGUAGE AND THE ROLE OF ARTIFICIAL INTELLIGENCE IN THIS PROCESS (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the factors for increasing the prestige of the Uzbek language as a state language and highlights the role of artificial intelligence technologies in this process. Regulatory legal documents adopted during the independence period are assessed as the main factor in strengthening the status of the language. Furthermore, the article examines the possibilities and existing challenges of artificial intelligence in integrating the Uzbek language into modern information and communication technologies and enhancing its scientific and technical potential. The research results outline the prospects for the digital transformation of the Uzbek language.
Keywords: State language, Uzbek language, artificial intelligence, digital transformation, language policy, linguistic resources, natural language processing.